ANNOBIC ANNOTATION OF ARABIC RSS FEED - Hendi, Hanaa Ghareib; Al-Feel, Haytham; Hassanein, Ehab E (MATTER: International Journal of Science and Technology, 2018)
Annotation is adding metadata to pages to become more meaningful and readable for machines. However, many Semantic annotation tools developed which proved their success in multiple languages, but Arabic is none of them. We present AnnoBic which is an Arabic semantic annotation tool for RSS feeds.